2022
DOI: 10.3390/nano12203652
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Antibacterial Properties of Chitosan-Fe3O4-AgNP Nanocomposite

Abstract: The goal of this research is to synthesize and characterize Fe3O4@Chitosan-AgNP nanocomposites in order to determine their antibacterial activity. The research methods include the synthesis of Fe3O4@Chitosan-AgNP nanocomposites, as well as the characterization of nanoparticles using scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) analysis, and subsequent antibacterial activity tests. The study’s findings demonstrated the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…For the sample CG11, four distinct peaks, located at 2θ = 11.9 • , 18.5 • , 23.4 • and 29.4 • , can be observed. These peaks are specific characteristic functional peaks of semi-crystalline chitosan, as shown in the literature [37,38].…”
Section: Resultssupporting
confidence: 55%
“…For the sample CG11, four distinct peaks, located at 2θ = 11.9 • , 18.5 • , 23.4 • and 29.4 • , can be observed. These peaks are specific characteristic functional peaks of semi-crystalline chitosan, as shown in the literature [37,38].…”
Section: Resultssupporting
confidence: 55%
“…These results demonstrated the formation of metal–phenolic coordination bonds between Fe 3 O 4 NPs and TA. [ 33 ] XRD analysis was used to further verify the existence of Fe 3 O 4 and the structural change upon formation of the hydrogel (Figure 1F), which exhibited the characteristic absorption peaks representing Fe 3 O 4 NPs and their 2θ values (25.0°, 35.8°, 43.4°, 57.3°, and 63.0°) releated to the standard Fe 3 O 4 reflections, including the highest peak, with a crystallographic plane (311) at 2θ = 35.8°, which was similar to the results of Hartati et al.. [ 34 ] The characteristic absorption peaks of Fe 3 O 4 also existed in the RSF/TA/Fe 3 O 4 hydrogels, with increasing Fe 3 O 4 concentrations resulting in higher intensities, demonstrating the existence of Fe 3 O 4 NPs. Moreover, the 2θ peak at 20.9° in the RSF/TA/Fe 3 O 4 hydrogels indicated the formation of a β‐sheet structure.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs are versatile regarding their antibacterial activity, meaning that they have a strong antifungal and antibacterial effect on different strains of bacteria. Studies reported that they present a strong antibacterial effect on Gram-negative bacteria such as Escherichia coli ( E. coli ) [ 14 ], Vibrio anguillarum [ 15 ], on Gram-positive bacteria such as Bacillus cereus [ 16 ], Staphylococcus aureus ( S. aureus ) [ 17 ] and even on fungi [ 18 , 19 ]. Since AgNPs are metal nanoparticles, the current trend is to combine them with more natural, biodegradable compounds to improve their biocompatibility, to enhance their chances to be tolerated better by tissues and to offer them support.…”
Section: Introductionmentioning
confidence: 99%